Dampak Pemilihan Prodi Terhadap Motivasi Belajar Mahasiswa PAI Angkatan 2024: 1. Alasan Mahasiswa PAI angkatan 2024 memilih Program Studi Pendidikan Agama Islam 2. Motivasi belajar mahasiswa PAI angkatan 2024 setelah memilih Program Studi Pendidikan Agama Islam 3. Dampak pemilihan Program Studi Pendidikan Agama Islam terhadap motivasi belajar mahasiswa PAI angkatan 2024 - Tina Desriani; Zahriyah Simargolang (Qolamuna : Jurnal Studi Islam, 2026)
This study aims to determine the reasons why students choose the PAI Study Program, describethe students' learning motivation after choosing the PAI Study Program and analyze the impactof study program selection on the learning motivation of PAI BP 24 students. This type ofresearch uses a qualitative approach with phenomenological methods. The main informants inthis study are PAI BP 24 students and supporting informants are PAI Lecturers and PAIAcademic Staff of UNP. Data were collected through observation, interviews anddocumentation. The results of this study indicate that the reasons why students choose the PAIStudy Program are the desire to deepen religious knowledge, aspirations from the beginning, andpurely because of their own desires, inspired by teachers, parental recommendations, linear withprevious schools, and job opportunities. The motivation of PAI UNP students is high, medium,low and even fluctuates. Overall, the choice of PAI study program has a significant impact onstudent learning motivation, both positive and negative impacts. Keywords : Study Program Selection, Learning Motivation, Islamic Education Students